Evaluación de la recuperación de Suelos en Taludes de Terrazas de banco con Pasto Gramalote (paspulum fasciculatum), aplicando dos tipos de Abonos y cuatro distancias de Siembra en Salache, Cotopaxi 2019-2020. - Mera Vizcaíno, Richard Alfredo (2020)
The research resulted from the need to seek an alternative to the protection of slopes in bank terraces as a soil conservation practice, generating benefits in results and implementation of a forage species; It was carried out in a practical way, on slopes located in the Agricultural Sciences and Natural Resources School (CAREN). The objectives were: To evaluate the density of plantation and optimal organic fertilizer for the performance of Gramalote grass (Paspulum fasciculatum) in the recovery of soils on slopes; Study agronomic variables between treatments; Analyze the physical-chemical values of the soil for each The objectives were: To evaluate the density of plantation and optimal organic fertilizer for the performance of Gramalote grass (Paspulum fasciculatum) in the recovery of soils on slopes; Study agronomic variables between treatments; Analyze the physical-chemical values of the soil for each treatment, to carry out the objectives, a completely randomized block design (DBCA) was proposed; being the Fertilizer Factors (Sheep, Bovine, Control) and the sowing distances (25, 30, 35, 40 cm) giving a total of 12 treatments and 3 repetitions. The evaluation of the factors served in the crop to determine the coverage and anchoring of the soil thus avoiding erosion, thus, the alternative hypothesis is accepted where it should be noted that at least one treatment had a significant impact on the rest of the treatments giving good results being this Sheep Manure and the distance of sowing the pasture of 30 and 40cm and being generated as a viable alternative for proper agricultural management on slopes. In the physical-chemical properties it is possible to differentiate how structural changes have been achieved and increase in main elements of importance in the development of plants, such as the addition of Phosphorus, presenting a significant difference between the initial and final soil. The texture that was presented at the end of the crop cycle thanks to the management was Franco and Franco Sandy, with a predominance in sand since the sector where the research was carried out has soils with high amounts of sand and erosive clays with high alkalinity, a correct management In the physical-chemical properties it is possible to differentiate how structural changes have been achieved and increase in main elements of importance in the development of plants, such as the addition of Phosphorus, presenting a significant difference between the initial and final soil. The texture that was presented at the end of the crop cycle thanks to the management was Franco and Franco Sandy, with a predominance in sand since the sector where the research was carried out has soils with high amounts of sand and erosive clays with high alkalinity, a correct management of covers and addition of organic matter facilitates the structural change in a soil and avoids partial or total erosion.